A Study of Hypermethylated Circulating Tumor DNA as a Universal Colorectal Cancer Biomarker. (6th January 2020) - Garrigou, Sonia; Perkins, Geraldine; Garlan, Fanny; Normand, Corinne; Didelot, Audrey; Le Corre, Delphine; Peyvandi, Sanam; Mulot, Claire; Niarra, Ralph; Aucouturier, Pascaline; Chatellier, Gilles; Nizard, Philippe; et al.
Abstract: BACKGROUND: Circulating tumor DNA (ctDNA) has emerged as a good candidate for tracking tumor dynamics in different cancer types, potentially avoiding repeated tumor biopsies. Many different genes can be mutated within a tumor, complicating procedures for tumor monitoring, even with highly sensitive next-generation sequencing (NGS) strategies. Droplet-based digital PCR (dPCR) is a highly sensitive and quantitative procedure, allowing detection of very low amounts of circulating tumor genetic material, but can be limited in the total number of target loci monitored. METHODS: We analyzed hypermethylation of 3 genes, by use of droplet-based dPCR in different stages of colorectal cancer (CRC), to identify universal markers for tumor follow-up. RESULTS: Hypermethylation of WIF1 (WNT inhibitory factor 1) and NPY (neuropeptide Y) genes was significantly higher in tumor tissue compared to normal tissue, independently of tumor stage. All tumor tissues appeared positive for one of the 2 markers. Methylated ctDNA (MetctDNA) was detected in 80% of metastatic CRC and 45% of localized CRC. For samples with detectable mutations in ctDNA, MetctDNA and mutant ctDNA (MutctDNA) fractions were correlated. During follow-up of different stage CRC patients, MetctDNA changes allowed monitoring of tumor evolution. CONCLUSIONS: These results indicate that MetctDNA could be used as a universal surrogate marker for tumor follow-up in CRC patients, and monitoring MetctDNA by droplet-based dPCR could avoid the need for monitoring mutations.